Influence of cyclic moderate intensity work on functional fitness of 17-21 years old students with “high” content of fat component - Furman, Y.M.; Brezdenyuk, O.Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: determination of run loads purposefulness in aerobic energy supply mode for increasing of functional fitness of 17-21 years old boys with high content of fat component. Material: 17 boys of 17-21 years’ age, who did not practice sports, participated in the researches. By their health all boys were belonged to main health group. During 24 weeks training cycle, at different stages of the research (in 8, 16 and 24 weeks from the beginning of training) we registered indicators of aerobic performance and component composition of body mass. Results: with trainings’ periodicity of 3 times a week energy losses for one training did not exceed maximal admissible value and exceeded minimal one. Minimal value was not less than 44% from maximal admissible energy losses (energy losses of one training were approximately 50% from maximal admissible). Conclusions: run loads in aerobic energy supply mode confidently increase boys’ aerobic potentials after 16 weeks of trainings. With it they do not influence on anaerobic performance. It was found that under influence of such trainings fat component of body mass and visceral fat reduce; muscular component increases. Alongside with it body mass index and main metabolism did not change for 24 weeks of trainings.